Investigation on tensile properties of polylactide-nanoclay (PLA/ MMT) surface modification nanocomposites - Rajamanikam, Sharvien; Royan, Nishata Royan Rajendran; Ab Ghani, Mohd Hafizuddin; Ismail, Ismayadi; Nawang, Rosnah; Che Abdullah, Che Azurahanim (UiTM Press, 2024)
Polylactic acid (PLA) has gained significant attention as an environmentally friendly biopolymer, but its limited mechanical properties have hindered broader applications. Nanoparticles such as montmorillonite (MMT) offer a promising approach to address this limitation. The intercalation of MMT with polymer chains can significantly impact the mechanical properties of the nanocomposites. Hence, this paper investigated the effect of surface-modified montmorillonite (MMT) nanoparticles on the mechanical properties of polylactic acid (PLA) nanocomposites. The acetylation process of MMT was carried out followed by neutralisation process with NaOH. PLA granules and acetylated-modified MMT were mixed, crushed into granular form, and moulded. The effect of varying concentrations of modified MMTs on the tensile strength, elongation at break, and maximum force of PLA/MMT nanocomposites was evaluated using the ASTM D638 standard. FTIR results showed shifts in peak intensities in regions 2750 cm-1- 2810 cm-1 led to changes in the aliphatic and aromatic regions, which confirmed the presence of acetylation. Controlled surface modification improved interfacial interactions and load distribution, enhancing overall mechanical performance. The incorporation of surface-modified MMT in PLA/MMT nanocomposite increased the maximum force, Young’s modulus, elongation at breaks and tensile strength. PLA/1wt% MMT and the PLA/7wt% MMT compositions exhibited good mechanical properties. However, the PLA/5 wt% MMT blend is deemed more suitable for food applications, such as disposable cups, plates, and cutleries, due to its lower elongation point. In conclusion, the hydrophilic properties of MMT and the hydrophobic properties of PLA are compatible due to the synergistic effects during surface modification which enhance the overall performance of the nanocomposites.